TUGAS LEMBAGA PERLINDUNGAN ANAK KABUPATEN PROBOLINGGO DALAM PENANGANAN EKSPLOITASI EKONOMI TERHADAP ANAK DI BAWAH UMUR - Hitaminah, Khusnul; Askandar, Achmad Syamsul; Umroh, Rofiatul (STIH Zainul Hasan Kraksaan Kraksaan, 2023)
ABSTRACT This research aims to describe the duties of the Probolinggo Regency Child Protection Agency in handling economic exploitation of children. Nowadays, the majority of children in Indonesia have a bleak fate, especially in the Probolinggo Regency area, this is because children have to face the bitterness of life on the streets, where children are forced to go out on the streets to earn a living because they have become the backbone of the family. Data collection in this research is normative empirical, namely a method that combines normative legal elements and is then supported by the addition of empirical data or elements. The method used in this research is qualitative descriptive, namely by tracing related documents and interviewing directly with the Chair of the Probolinggo Regency Child Protection Agency. The research results show that the task of the Child Protection Agency in handling economic exploitation of minors is to carry out prevention, handle report responses, protect children, society, carry out supervision and advocacy, carry out rehabilitation and support, develop policies and regulations, implement training and capacitation, maximizing education and awareness programs for the community, carrying out research and data collection and providing legal assistance. The obstacles that will be overcome in taking action to deal with economic exploitation of children are lack of resources which include adequate budgets, trained personnel, infrastructure and equipment, lack of understanding or ignorance, challenges in obtaining cooperation and partnerships, stigma and fear: Children who become Victims of economic exploitation often face stigma and fear in reporting cases or seeking help, weak legal systems, social and cultural factors, mobility and migration. Keywords: Treatment, Economic Exploitation, Children